Коллектор электрической машины - Бекишев Р. Ф. Рудольф Фридрихович; Бокман Г. А. Григорий Аронович; Данекер В. А. Валерий Аркадьевич; Качин С. И. Сергей Ильич; Лебедев С. И. Сергей Иванович; Ситников С. А. Сергей Александрович; Шуршаков А. Н. Анатолий Николаевич
опубл. 15.01.81